171 Inhibition of pure culture Salmonella Newport by camphor and eucalyptol in vitro. (30th November 2020) - Seidel, Darren S; Pisani, Kristen; Hunnicutt, Austin; Banks, Quinterrius; Callaway, Todd
Abstract: Volatile oils have potent antimicrobial activities that have allowed them to be used as food preservatives for millennia. The impact of concentrations of the monoterpene volatile oils camphor and eucalyptol on the growth of the cattle and foodborne pathogen Salmonella Newport was evaluated by examining changes in optical density (600 nm). Cultures of S. Newport were grown in Tryptic Soy Broth (TSB) overnight and inoculated into fresh TSB tubes at an initial concentration of ~106 CFU/mL in the presence of monoterpene concentrations (0 – 9.85 mM) and were incubated at 39℃. Final optical density and maximum specific growth rates (h-1) were determined. Data were analyzed using a PROC GLM procedure in SAS 9.4 for a 2*5 repeated measure factorial. Overall, there was a concentration (P < 0.01) and a time by concentration (P < 0.01) effect, but no differences between monoterpene types (P = 0.28) were observed. Camphor and eucalyptol concentrations of 3.28 and 9.85 mM reduced (P < 0.05) S. Newport growth. The highest dose (9.85 mM) of camphor and eucalyptol immediately inhibited S. Newport growth. Maximum specific growth rate was reduced (P < 0.01) by both monoterpenes compared to controls, most particularly at 9.85 mM concentrations, but were not different between the two monoterpenes. Collectively, our results suggest that monoterpenes at high concentrations can reduce the growth of Salmonella Newport; however, to fully understand practical implementation of monoterpene effects on foodborne or animal pathogens, studies using both mixed culture and in vivo models are needed. Tuesday, July 21, 2020